Profil Kepuasan Pasien terhadap Pelayanan Kefarmasian di Klinik Mabarrot MWC NU Wringinanom - Tawakal, Muhamad Aulia Putra; Anwari, Farida; Amarullah, Adinugraha; Aaliyah, Reza (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
The health service system is tasked with providing services to patients related to pharmaceutical preparations, including pharmaceutical services. If the procedure is in accordance with the standards and codes of ethics that have been set, health services can satisfy every patient. Patient satisfaction surveys are needed to improve the quality of service, and satisfaction is the level of patient feelings that arise as a result of the performance of health services obtained after the patient compares it with what he expects. The purpose of this study was to determine how satisfied patients are with the pharmaceutical services they receive at the Mabarrot MWC NU Wringinanom Clinic by looking at the level of performance and expectations. Sampling is based on the Purposive Sampling technique. The five dimensions of satisfaction, namely reliability, responsiveness, assurance, empathy, and tangibility, each have four question items from 20 questionnaire questions. With the results of the study, a score of 3.32 indicates that they are very satisfied with patient expectations, and a score of 3.15 indicates that they are said to be satisfied with performance.